Pengaruh Model Inkuiri Terbimbing Dalam Penerapan Rasio Dalam Kehidupan Sehari-Hari Untuk Meningkatkan Berpikir Kritis Siswa Kelas 6 SD - Azis Farkhan; Cholifatur Rosidah; Rosmiati Rosmiati (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
The aim of this research is to determine the effect of using a guided inquiry learning approach on the development of critical thinking skills in sixth grade elementary school in Mathematics. This research uses a quantitative approach with the ex post facto method, namely the researcher does not control the variables, only takes data regarding the influence of the independent variable on the dependent variable. This research uses a quantitative approach and the analysis in this research uses descriptive and regression analysis. This research was motivated by teachers' difficulties in providing a good understanding of grade 6 elementary school mathematics learning material on the application of ratios in everyday life, namely scales. teachers' limited knowledge regarding the application of inquiry-based learning methods, as well as students' low critical thinking abilities in mathematics learning and their overall low academic achievement. The population in this study were 77 grade VI students at Wadungasri Elementary School, Waru District, Sidoarjo Regency, and a sample of 25 students was taken. Data collection techniques using questionnaires. Data processing techniques with validity testing using expert judgment techniques. Reliability test uses Alpha Cronbach. Analysis prerequisite tests are normality test and linearity test. The data analysis technique used is a simple regression test. Research results: the guided inquiry learning model has an effect on students' critical thinking skills by 1.673%.